Hydrochemical and isotopic properties of the groundwater in the middle part of the Tulián river watershed, Puerto Cortés, Honduras - Contreras, Tirza C. (2011)
The present study identifies the hydrochemical and isotopic properties of 11 springs, including one thermal spring, in Tulian watershed, located in the city of Puerto Cortés, Cortés, Honduras. The relation between the concentrations of the environmental stable isotopes deuterium (2H) and oxygen – 18 (18O) in the water is similar to the relation in global meteoric water, indicating that the water has a meteoric origin. Evaluation of the geochemical characteristics of the water reveals that these springs belong to the same hydrogeological system, which comprises a fractured schist and gneiss of the Esquistos Cacaguapa formation. The water of the evaluated springs is mainly Na - Ca - HCO3. The δ2H (‰) and δ2H contents indicate that there is no variation in the ‰ value.